Safety and Feasibility of Robotic Natural Orifice Specimen Extraction Surgery in Colorectal Neoplasms During the Initial Learning Curve - Yao, Hongliang; Li, Tiegang; Chen, Weidong; Lei, Sanlin; Liu, Kuijie; Jin, Xiaoxin; Zhou, Jiangjiao (Frontiers in Oncology, 2020)
Aim: To analyze the learning curve (LC) for robotic natural orifice specimen extraction surgery (NOSES) for colorectal neoplasms and evaluate safety and feasibility during the initial LC. Method: Patients who consecutively underwent robotic NOSES performed by two surgeons between March 2016 and October 2019 were analyzed retrospectively. The operation time was evaluated using the cumulative sum method to analyze the LC. The clinicopathological data before and after the completion of LC were extracted and compared to evaluate safety and feasibility. Results: In total, 99 and 66 cases were scheduled for robotic NOSES by Prof. Yao and Prof. Li, respectively. The peak points of LC were observed at the 42nd and 15th cases of Yao and Li respectively, then operation time began to decrease. Only the operation time for Yao before the completion of LC (213.3 ± 67.0 min) was longer than that after the completion of LC (143.8 ± 33.3 min). For Yao nor for Li, other indices, such as postoperative hospital stay, intraoperative blood loss, conversion to laparotomy, incidence of anastomotic leakage, reoperation rate, and 90-day mortality rate lacked significant statistical differences（P＞0.05）. In terms of feasibility, the number of lymph nodes harvested, positive resection margin rate, and total cost before and after the completion of LC had no significant statistical difference (P ＞ 0.05). Conclusion: The cases before the completion of LC for robotic NOSES in colorectal neoplasms varied from 15 cases to 42 cases. Robotic NOSES is safe and feasible during the initial LC.